Rachel Dixon (2022) Infanticide: Expert Evidence and Testimony in Child Murder Cases, 1688-1955. London: Routledge - Victoria Nagy (International Journal for Crime, Justice and Social Democracy, 2023)
Victoria Nagy reviews Infanticide: Expert Evidence and Testimony in Child Murder Cases, 1688-1955 by Rachel Dixon.